Long-term response of coastal macrofauna communities to de-eutrophication and sea level rise mediated habitat changes (1980s versus 2018) - Singer, Anja; Bijleveld, Allert I.; Hahner, Florian; Holthuijsen, Sander J.; Hubert, Krischan; Kerimoglu, Onur; Kleine Schaars, Loran; Kröncke, Ingrid; Lettmann, Karsten A.; Rittweg, Timo; Scheiffarth, Gregor; van der Veer, Henk W.; et al. (Frontiers in Marine Science, 2023)
A statistical community analysis, performed for the East-Frisian Wadden Sea (EFWS, southern North Sea), revealed significant quantitative and spatial changes in the characteristic macrofauna communities between the 1980s and 2018, most likely in response to de-eutrophication and sea level rise mediated habitat changes. Historical macrofauna data from the Quantitative Sensitivity Mapping (1980s, SENSI 1) were reanalyzed and compared with data from the Synoptic Intertidal Benthic Survey (SIBES/SENSI 3) collected in 2018. Since the 1980s, the total number of taxa remained relatively stable (1980s: 90, 2018: 81), but the total abundance decreased by ca. -31% and the total biomass decreased by ca. -45%, particularly in the eastern regions of the study site probably due to de-eutrophication processes. Thereby, the mean abundances/m² of ≥ -80% (1980s-2018) in the EFWS of several dominant species decreased: e.g. the gastropod Peringia ulvae, the polychaete Lanice conchilega and the bivalve Mya arenaria. In contrast, the mean abundance/m² of one dominant species increased by ≥ +80% (1980s-2018): the invasive bivalve Ensis leei. The mean biomass [g/m²] of three dominant species decreased by ≥ -80% (1980s-2018): P. ulvae, L. conchilega and the amphipod Corophium volutator. In contrast, the mean biomass of one dominant species increased by ≥ +75% (1980s-2018): the polychaete Arenicola marina. In the western part of the EFWS, not only higher abundances of A. marina, but also of L. conchilega and P. ulvae were found in 2018, caused i.a. by decreased mud contents and sediment accretion on tidal flats. At the community level, the Oligochaeta/Heteromastus community increased in spatial distribution in the western EFWS in 2018 in the vicinity of increasing mussel/oyster beds. Morphodynamic changes due to sea level rise mediated sediment accretion and increased hydrodynamics and/or dredging activities seemed to have caused these habitat changes in particular in the Ems-Dollart estuary.